KEDUDUKAN PUTUSAN PENGADILAN TERHADAP PRINSIP LIMITED COURT INVOLVEMENT MENURUT UNDANG-UNDANG NO. 30 TAHUN 1999 TENTANG ARBITRASE DAN ALTERNATIF PENYELESAIAN SENGKETA (STUDI KASUS PUTUSAN No. 238.PK/PDT/2014) (Lex Jurnalica, 2018)
AbstractThe Law of the Republic of Indonesia Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution expressly states in Article 11 paragraph (2) that the District Court must refuse and will not interfere in a dispute settlement that has been determined by arbitration, except in the case of certain things stipulated in this Law. This is the basis of the principle of limited court involvement which limits the authority of the court in deciding a case. However, in practice there were still found District Courts that decided the case despite the arbitration clause in the agreement of the parties. In addition to the secrecy of the parties revealed in the Court, legal certainty regarding the principle of the limited court involvement does not work. The author raises two problems from this study, namely: a. How is the application of the principle of limited court involvement in court institutions in Indonesia ?; b. How is the legal position of the Court's Decision on the principle of limited court involvement arbitration (Case Study of Decision No. 238.PK/Pdt/2014)? In this study the author uses the method of writing juridical-normative law accompanied by primary and secondary legal materials. Based on the results of the study, the authors found that the problems that occur between the parties are a unity in the arbitration agreement, and this cannot be separated from the principle of limited court involvement because it is still within the scope of the arbitration agreement. At the end of this study, the author concluded that there was a real judge's mistake in deciding the disputes of the parties in the case above. This research is expected to increase the readers' insight about the principle of the limited court involvement as well as a reflection of applicable positive law.Â Keywords: principles of limited court involvement, arbitration, district courtsÂ AbstrakUndang-undang Republik Indonesia Nomor 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa secara tegas menyatakan dalam Pasal 11 ayat (2) menyebutkan bahwa Pengadilan Negeri wajib menolak dan tidak akan campur tangan di dalam suatu penyelesaian sengketa yang telah ditetapkan melalui arbitrase, kecuali dalam hal-hal tertentu yang ditetapkan dalam Undang-undang ini. Hal ini merupakan dasar dari prinsip limited court involvement yang membatasi kewenangan pengadilan dalam memutuskan suatu perkara. Namun demikian, pada prakteknya masih ditemukan Pengadilan Negeri yang memutuskan perkara meskipun terdapat klausul arbitrase dalam perjanjian para pihak. Selain kerahasiaan para pihak yang terkuak dalam Pengadilan, kepastian hukum tentang prinsip limited court involvement ini pun tidak berjalan. Penulis mengangkat dua permasalahan dari penelitian ini yaitu : a.Bagaimana penerapan prinsip limited court involvement dalam lembaga pengadilan di Indonesia?; b. Bagaimana kedudukan hukum Putusan Pengadilan terhadap prinsip limited court involvement arbitrase (Studi Kasus Putusan No. 238.PK/Pdt/2014)? Dalam penelitian ini penulis memakai metode penulisan hukum yuridis-normatif yang disertai bahan hukum primer dan sekunder. Berdasarkan hasil penelitian, penulis mendapatkan bahwa permasalahan yang terjadi antara para pihak merupakan satu kesatuan dalam perjanjian arbitrase, dan hal ini tidak dapat dipisahkan dengan prinsip limited court involvement karena masih dalam ruang lingkup perjanjian arbitrase. Di akhir penelitian ini, penulis menyimpulkan bahwa terdapat kekeliruan hakim yang nyata dalam memutuskan sengketa para pihak dalam perkara diatas. Penelitian ini diharapkan dapat menambah wawasan pembaca tentang prinsip limited court involvement serta menjadi refleksi hukum positif yang berlaku.Â Kata kunci: prinsip limited court involvement, arbitrase, pengadilan negeri